Sustainability and the future of work and entrepreneurship for the underserved - Crump, Micah; Rolle, Jo-Ann (IGI Global, 2022)
"This book highlights marginalized labor and entrepreneurial market segments and reviews strategies used to prepare for technology changes globally with the intent to provide a series of recommendation by thought leaders that may aid in growing and sustaining a more inclusive global society.